Sacrificio de animales y libertad religiosa. Comentario a Centraal Israëlitisch Consistorie Van België, STJUE (Gran Sala) de 17-12-2020 - Agustín García Ureta (Revista Vasca de Administración Pública, 2021)
This comment examines a judgment of the Court of Justice of the European Union (CJEU) (Grand Chamber) regarding the restrictions for the ritual slaughter of animals, in the light of the EU regulations on this matter. Unlike previous judgments, the CJEU has affirmed that the Member States are entitled to impose further restrictions, such as the previous reversible stunning of animals without causing their death. The lack of common consensus on this matter in the EU has led the CJEU not to set out a judicial canon on this matter.